2020
DOI: 10.1021/jacs.0c00768
|View full text |Cite
|
Sign up to set email alerts
|

Design, Optimization, and Study of Small Molecules That Target Tau Pre-mRNA and Affect Splicing

Abstract: Approximately 95% of human genes are alternatively spliced, and aberrant splicing events can cause disease. One pre-mRNA that is alternatively spliced and linked to neurodegenerative diseases is tau (microtubule-associated protein tau), which can cause frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP-17) and can contribute to Alzheimer's disease. Here, we describe the design of structure-specific lead small molecules that directly target tau pre-mRNA from sequence. This was followed by hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 77 publications
0
64
1
Order By: Relevance
“…118 Additional structure-activity relationships (SAR) were used to optimize MTX's ability to decrease exon 10 inclusion, leading to compounds with enhanced affinity for tau pre-mRNA and increased potency for reducing the levels of 4R tau (Table S1, ESI †). 119 More recently, Chen et al 120 reported that stabilizing the SRE by small molecule binding to the A bulge present in the SRE structure could inhibit recognition by U1 snRNP and promote exon 10 exclusion in wild-type (WT) and DDPAC tau. Tanimoto score-based similarity searching using a previously reported Inforna hit 121 as a query identified A-1 as a modulator of the 4R/3R tau ratio ( Fig.…”
Section: Small Molecule Modulation Of Mapt Pre-mrna Splicingmentioning
confidence: 99%
See 1 more Smart Citation
“…118 Additional structure-activity relationships (SAR) were used to optimize MTX's ability to decrease exon 10 inclusion, leading to compounds with enhanced affinity for tau pre-mRNA and increased potency for reducing the levels of 4R tau (Table S1, ESI †). 119 More recently, Chen et al 120 reported that stabilizing the SRE by small molecule binding to the A bulge present in the SRE structure could inhibit recognition by U1 snRNP and promote exon 10 exclusion in wild-type (WT) and DDPAC tau. Tanimoto score-based similarity searching using a previously reported Inforna hit 121 as a query identified A-1 as a modulator of the 4R/3R tau ratio ( Fig.…”
Section: Small Molecule Modulation Of Mapt Pre-mrna Splicingmentioning
confidence: 99%
“…Notably, this assertion is bolstered by studies that direct the splicing outcome of MAPT exon 10 (tau), another IDP. 120 10. Targeted cleavage of diseasecausing RNAs using bleomycin A5-conjugates…”
Section: Small Molecules Inhibit Translation Of Traditionally Undruggmentioning
confidence: 99%
“…Besides ASO-based tau expression inhibitors, drug molecules that induce the exon 10 skipping in the mutant MAPT would also be of potential therapeutic interest for restoring the aberrant splice pattern for FTDP-17 [ 9 ]. ASOs bound to either the 5′ or 3′ splice site of exon 10 were demonstrated to induce exon 10 skipping [ 76 ].…”
Section: Known Rna-targeting Splicing Modifiers For the Treatment Of Human Diseasesmentioning
confidence: 99%
“…NMR experiments demonstrated that mitoxantrone stabilizes the stem-loop structure through intercalating into the stem base [ 145 ]. Several other small-molecule splicing modifiers were identified by the Disney group via structure-based design [ 9 , 79 ] or phenotypic screening (e.g., “compound 9” and “compound 2” from the original report [ 9 ] ( Figure 8 b). Compound 9 was shown to stabilize an internal bulge of the stem-loop structure and reduce exon 10 splicing [ 9 ].…”
Section: Known Rna-targeting Splicing Modifiers For the Treatment Of Human Diseasesmentioning
confidence: 99%
See 1 more Smart Citation